FEATURES OF THE COURSE OF RELAPSES TUBERCULOSIS IN THE POLTAVA REGION - Yareshko, A.G.; Boyko, N.G.; Kulish, M.V.; Vorodyuhina, A.K.; Bezruchko, D.V. (World of Medicine and Biology, 2013)
To study the epidemiological situation and the characteristics of the course of relapses tuberculosis in the Poltava region were analyzed statistics for the last 5 years and was evaluated by relapses of disease in 145 patients. The results showed that in last years there has been an increase in the number of relapses in the Poltava region. Most cases are detected in bad time. Every year there is an increase in the number of destructive, bacillary, drag resistant form of relapses tuberculosis.